The Relationship between Moral Education in the Family and Adolescent Personality - Arifin, Syamsul; Abuorabe, Marwan; Agail, Omer (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine whether there is a relationship between moral education in the family and adolescent personality. Methodology: This study uses questionnaire methods, documentation and data analysis methods. The subjects of the study were 40 respondents, using population and sample techniques (purposive random sampling). Data collection used a questionnaire instrument to collect x and y data. The collected research data were analyzed using descriptive statistical analysis techniques. Testing the research hypothesis used correlation analysis. Main Findings: The results of the study showed that at the 5% level = 0.313. So that the comparison obtained based on the table of values ​​obtained is: 0.219 <0.313 at a significant level of 5%. From the analysis of the data, the working hypothesis (Ha) which states that there is a significant relationship between moral education in the family and adolescent personality is rejected. At the 1% level = 0.405, the comparison obtained based on the table of values ​​obtained is: 0.219 <0.405, then the null hypothesis (Ho) which states that there is no positive relationship between moral education in the family and adolescent personality so that Ho is accepted. Novelty/Originality of this study: This study integrates moral education in the family as one of the determining factors in the formation of adolescent personality. Although many studies discuss moral education and adolescent development separately, this study offers a more comprehensive approach, considering how the family environment plays a direct role in shaping adolescent moral values ​​and behavior.